BUDAYA KINERJA LEMBAGA PELAYANAN PUBLIK: Analisis Budaya Kinerja Kementrian dan LPNK di Indonesia (PERFORMANCE CULTURE IN PUBLIC SERVICE ORGANIZATION: An Analysis of Performance Culture ini Ministries and Non Ministerial Institutes in Indonesia) - Sri Wahyu Wijayanti (Jurnal Borneo Administrator, 2013)
Performance of public service in Indonesia is still not satisfactory. This has been caused by the low performance culture in the public service. In this paper, service performance culture is elaborated into three dimensions, namely the commitment to service quality, performance reward and attention toward stakeholders. The analysis of quantitative data concerning the performance culture obtained from a survey of 54 ministries and the Non-Ministerial Government Institute in Indonesia indicated that performance culture of the Ministry and Institute does not support the creation of public service quality. Thus, improvements of performance culture in public service organizations in Indonesia should be managed by improving the performance culture of public service institution.Keywords: cultural performance, public service institutions, ministries, non-ministerial government institutions.Kinerja lembaga pelayanan publik di Indonesia saat ini masih belum memuaskan. Hal ini berhubungan dengan budaya kinerja yang berkembang dalam lembaga pelayanan publik tersebut. Dalam tulisan ini budaya kinerja pelayanan dielaborasi kedalam tiga dimensi yakni komitmen terhadap kualitas pelayanan, penghargaan terhadap kinerja dan perhatian terhadap pemangku kepentingan. Hasil analisis atas data-data kuantitatif mengenai budaya kinerja yang didapatkan dari survei terhadap 54 Kementerian dan Lembaga Pemerintah Non-Kementerian (LPNK) di Indonesia, menunjukkan bahwa budaya kinerja Kementrian dan K/L saat ini masih belum mendukung terciptanya pelayanan publik yang berkualitas.Dengan demikian perbaikan budaya kinerja pada lembaga pelayanan publik di Indonesia sudah seharusnya dilakukan melalui perbaikan budaya kinerja lembaga pelayanan publik.Kata kunci: budaya kinerja, lembaga pelayanan publik, kementerian, lembaga pemerintah Non-Kementerian